"Red-Green Fusion" and "Local Narrative": Scene Innovation and Path Exploration for the Zhaoqing Red Research-Based Learning Curriculum System - Li, Yingmei; Liu, Yuchen; He, Dongjin (International Journal of Natural Resources and Environmental Studies, 2025)
As a vital practical form of the "Big Ideological and Political Course," red research-based learning is at a critical juncture, transitioning from "high-speed development" to "high-quality development." However, current practices in red research-based learning generally suffer from bottlenecks such as curriculum design homogenization, superficial educational scenes, and alienated emotional experiences, making it difficult to achieve the fundamental goal of value guidance. Using Zhaoqing City’s rich red culture, ecological resources, and local intangible cultural heritage as a case study, this article focuses on solving the challenges of "localization" and "contextuality" in research-based learning curricula. The study innovatively proposes two core strategies: "Red-Green Fusion" and "Local Narrative." "Red-Green Fusion" aims to break down the barriers between red education and ecological civilization education, using Zhaoqing’s "green mountains and waters" as a narrative space and value extension for its "revolutionary red." "Local Narrative" advocates for using Zhaoqing’s unique intangible cultural heritage (such as Zongzi and Duan Inkstones) as cultural "metaphors" and emotional "media" to translate grand red spirits into perceivable and tangible embodied experiences. Through qualitative analysis and theoretical construction, this article deeply explores the internal mechanisms by which these two strategies drive the innovation of "educational scenes" in research-based learning. Based on this, it constructs a three-dimensional curriculum implementation path of "cognitive awakening—contextual immersion—value re-creation." This research aims to provide a replicable design paradigm for the "localization" of red research-based learning curricula for Zhaoqing and other similar cities, intending to genuinely activate comprehensive local resources and promote the transformation of red research-based learning from a superficial "glance-and-go" tour to a profound "heart-and-soul" educational experience.